Are there clinically relevant anatomical differences of the proximal femur in patients with mild dysplastic and primary hip osteoarthritis?: a CT-based matched-pairs cohort study - Innmann, Moritz Maximilian; Merle, Christian (Clinical radiology, 2019)
AIM - To investigate the three-dimensional anatomy and shape of the proximal femur, comparing patients with secondary osteoarthritis (OA) due to mild developmental dysplasia of the hip (DDH) and primary hip OA. - MATERIALS AND METHODS - This retrospective radiographic computed tomography (CT)-based study investigated proximal femoral anatomy in a consecutive series of 84 patients with secondary hip OA due to mild DDH (Crowe type I&II/Hartofilakidis A) compared to 84 patients with primary hip OA, matched for gender, age at surgery, and body mass index. - RESULTS - Men with DDH showed higher neck shaft angles (127±5° vs. 123±4°; p<0.001), whereas women with DDH had a larger femoral head diameter (46±4 vs. 44±3 mm; p=0.002), smaller femoral offset (36±5 vs. 40±4 mm; p<0.001), decreased leg torsion (25±13° vs. 31±16°; p=0.037), and a higher neck shaft angle (128±7° vs. 123±4°; p<0.001) compared to primary OA patients. Similar patterns of the three-dimensional endosteal canal shape of the proximal femur, but a high inter-individual variability for femoral canal torsion at the meta-diaphyseal level were found for DDH and primary OA patients. - CONCLUSION - Standard cementless stem designs are suitable to treat patients with secondary hip OA due to mild DDH; however, high patient variability and subtle anatomical differences in the proximal femur should be respected.
Available online 26 August 2019
Gesehen am 11.11.2019